PENGARUH EXPERIENTIAL MARKETING TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA PELANGGAN TOKOPEDIA (Studi Kasus pada Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang) - Ufairy, Mohammad Miqdad; Farida, Lailatul (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to determine the effect of experiential marketing on customer loyalty through customer satisfaction as an intervening variable for Tokopedia customers. This research approach uses a quantitative approach. The sampling method is purposive sampling. The sample is 102. The results (1) Sense (X1) and Feel (X2) get results that have an effect and are not significant on customer loyalty (Y). While Think (X3), Act (X4) and Relate (X5) get significant and influential results Customer loyalty (Y). (2) Sense (X1), Think (X3) and Act (X4) get acceptable results and not significant Customer Satisfaction (Z). Feel (X2) and Relate (X5) get acceptable and significant results. (3) Customer Satisfaction (Z). Customer Satisfaction (Z) is accepted and significant Customer Loyalty (Y). (4) Customer Satisfaction (Z) is accepted and significant to Customer Loyalty (Y) Keywords: Customer Loyalty, Experiential Marketing, Customer Satisfaction